Reputation and peacekeeping missions: Brazil and middle powers in challenging times (Revista da Escola de Guerra Naval, 2023)
International law has been barely focused on the reputational status,which may be represented as a complex of attributes based on theperception of the others, that can determine the state’s position in theinternational arena and cooperation scenarios. Thus, the opportunityof taking an active role in the international agenda makes Brazil andother middle powers and emerging markets as high-value partners,with an increasing and representative participation in internationalorganizations in the last years. In respect to the Brazilian case, thosefunctions that can be cited as determinants of reputation range fromthe peacekeeping mandates it has detained, to the candidacy as apermanent member of the United Nations Security Council. Thispaper is focused on providing a conceptual framework to explainthe enhancing of one actor’s international reputation based onPeacekeeping missions and considering Andrew Guzman´s typology(2001; 2010; 2011). This theme is an important way of thinkingpolitical gains in terms of international competition not only becauseit elucidates states’ conditions for obtaining success but, also, howeligible they are for projecting themselves besides military strength.In addition, the effectiveness and compliance ratio, either for theBrazilian case or other emerging markets, are not clear to a great partof the analysts. So, under the soft or hard law, the intention is to makean archeology of the reputation model that is connected to politicalgains in the Brazilian contemporary case, as to expand its internationalreliability and promote economic odds.